Current Status and Challenges in Radiology Education at Traditional Chinese Medicine Colleges (Asian Journal of Social Science Studies, 2024)
The importance of bridging the gap between traditional Chinese medicine (TCM)'s holistic approach and Western medicine's diagnostic technologies, particularly in the context of medical imaging. In this paper, we discussed the challenges faced by TCM colleges in radiology education in China include philosophical differences, resource constraints, faculty expertise variations, and language and cultural barriers. We advocate for the implementation of multifaceted strategies, such as enhancing the comprehensiveness of the syllabus, optimizing the radiology curriculum, and enriching internship experiences. These measures are designed to elevate the quality of radiology education, enhance student engagement, and improve learning outcomes within TCM colleges.